2020
DOI: 10.1093/ofid/ofaa439.1421
|View full text |Cite
|
Sign up to set email alerts
|

1236. Safety and Immunogenicity of a 20-Valent Pneumococcal Conjugate Vaccine (PCV20) in Healthy Infants in the United States

Abstract: Background A 20-valent pneumococcal conjugate vaccine (PCV20) is being developed to extend protection against pneumococcal disease beyond that of the 13-valent pneumococcal vaccine (PCV13). This is the first safety and immunogenicity study of PCV20 in healthy infants. Methods This randomized, double-blind study enrolled and randomized (1:1) healthy infants ≥ 42 to ≤ 98 days of age to receive a 4-dose series of either PCV20 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…30 IgG GMCs were lower for some serotypes after 2 infant doses in this study compared with 3 infant doses; however, functional antibodies were induced after the infant series for all serotypes, and IgG GMCs were largely similar for both regimens after the toddler dose, supporting effectiveness of both schedules. 30 To reduce the likelihood of rejecting a potentially effective PCV in a 3-dose series, particularly a higher valent PCV, it is crucial to consider supportive immunogenicity data for serotypes missing statistical NI criteria, consistent with WHO guidance. This is important considering that the 7 additional PCV20 serotypes are associated with severe/invasive disease and antibiotic resistance 17–21 and are estimated to cause 21%–42% of IPD in young children in Europe.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…30 IgG GMCs were lower for some serotypes after 2 infant doses in this study compared with 3 infant doses; however, functional antibodies were induced after the infant series for all serotypes, and IgG GMCs were largely similar for both regimens after the toddler dose, supporting effectiveness of both schedules. 30 To reduce the likelihood of rejecting a potentially effective PCV in a 3-dose series, particularly a higher valent PCV, it is crucial to consider supportive immunogenicity data for serotypes missing statistical NI criteria, consistent with WHO guidance. This is important considering that the 7 additional PCV20 serotypes are associated with severe/invasive disease and antibiotic resistance 17–21 and are estimated to cause 21%–42% of IPD in young children in Europe.…”
Section: Discussionmentioning
confidence: 45%
“…11,12,22,23 PCV20 induced robust immune responses and demonstrated a safety/tolerability profile similar to PCV13 in several adult and pediatric clinical trials. 24–32 This study assessed safety and immunogenicity of a 3-dose PCV20 series compared with PCV13.…”
mentioning
confidence: 99%
“…10,11,18-89 18 studies (20 publication records) were excluded from the analysis: 6 studies did not provide individual patient or aggregate data, [70][71][72][73] and 12 studies (14 publication records) were head-to-head studies with the vaccines of interest, but it was not possible to form a loop within the network meta-analysis to provide indirect evidence (See Supplementary Figure 1 and Supplementary Table 2). [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Of these 12 studies, 8 reported results from different PCVs including a new Cuban PCV7, PCV10-SII, PCV11, PCV12, a Chinese PCV13, PCV14, PCV15, PCV20, PCV24 and PCV SP0202-VI. The remaining 27 studies (53 publication records) from 2009 to 2022 were included in the network meta-analyses.…”
Section: Search Resultsmentioning
confidence: 99%
“…A study out of Spain found that the safety profile and efficacy of PCV administration in low birth weight and preterm infants was similar to term infants ( López-Sanguos et al, 2019 ) [M]. A similar study was done with healthy infants given the PCV20, and similar adverse effects to the PCV13 were noted ( Senders et al, 2020 ) [MC].…”
Section: Bacterial Vaccinesmentioning
confidence: 93%